RISK FACTORS FOR IMPAIRED BONE DENSITY IN MALE PATIENTS UNDERWENT HEMODIALYSIS DUE TO CHRONIC KIDNEY DISEASE - Patritius Kelik Dwi Santo Ismoyo; Sugeng Yuwana (Universitas Airlangga, 2018)
Background: Chronic kidney disease (CKD) is associated with impairment of mineral metabolism that, in turn, may result in the derangement of bone density, i.e. osteopenia or osteoporosis. Purpose: The objective of this study is to assess the impairment of bone density in male patients underwent routine hemodialysis due to stage V CKD.Methods: Subjects in this cross sectional study were male patients underwent routine hemodialysis in Hemodialysis Unit Dr. Sardjito General Hospital Yogyakarta in June 2014. Subjects were invited when they were over 18 years old and had undergone hemodialysis for at least 6 months. Bone density of lumbar spine, total hip and femoral neck were assessed using DEXA. We collected information on age and the etiology of the CKD from medical records. Body weight and height were measured using calibrated apparatus. Data were analyzed using OpenEpi.Results: We invited 30 male patients with mean (SD) age of 56.8 (13.8) years. Bone density of lumbar spine and femoral neck were significantly associated with the duration of hemodialysis, i.e. OR (95% CI) of 31.7 (3.8-856.0), p=0.0003 and 12.0 (1.9-111.0), p=0.005, respectively for those underwent hemodialysis of more than 12 months. Obesity was only protective for the bone density of the total hip, OR(95%CI) of 0.1 (0.004-0.9), p=0.03. There was no association between the etiology of the CKD and the decrease in bone density.Conclusion: This study observed significant association between the duration of hemodialysis and bone density.